Telmisartan Modulates Glial Activation: In Vitro and In Vivo Studies. - Nofar Torika; Keren Asraf; Abraham Danon; Ron N Apte; Sigal Fleisher-Berkovich (PLoS ONE)
The circulating renin-angiotensin system (RAS), including the biologically active angiotensin II, is a fundamental regulatory mechanism of blood pressure conserved through evolution. Angiotensin II components of the RAS have also been identified in the brain. In addition to pro-inflammatory cytokines, neuromodulators, such as angiotensin II can induce (through angiotensin type 1 receptor (AT1R)) some of the inflammatory actions of brain glial cells and influence brain inflammation. Moreover, in Alzheimer's disease (AD) models, where neuroinflammation occurs, increased levels of cortical AT1Rs have been shown. Still, the precise role of RAS in neuroinflammation is not completely clear. The overall aim of the present study was to elucidate the role of RAS in the modulation of glial functions and AD pathology. To reach this goal, the specific aims of the present study were a. to investigate the long term effect of telmisartan (AT1R blocker) on tumor necrosis factor-α (TNF-α), interleukin 1-β (IL1-β) and nitric oxide (NO) release from glial cells. b. to examine the effect of intranasally administered telmisartan on amyloid burden and microglial activation in 5X familial AD (5XFAD) mice. Telmisartan effects in vivo were compared to those of perindopril (angiotensin converting enzyme inhibitor). Long-term-exposure of BV2 microglia to telmisartan significantly decreased lipopolysaccharide (LPS) -induced NO, inducible NO synthase, TNF-α and IL1-β synthesis. The effect of Telmisartan on NO production in BV2 cells was confirmed also in primary neonatal rat glial cells. Intranasal administration of telmisartan (1 mg/kg/day) for up to two months significantly reduced amyloid burden and CD11b expression (a marker for microglia) both in the cortex and hipoccampus of 5XFAD. Based on the current view of RAS and our data, showing reduced amyloid burden and glial activation in the brains of 5XFAD transgenic mice, one may envision potential intervention with the progression of glial activation and AD by using AT1R blockers.